Electron transfer reactions of RuIII(edta) containing the n-heterocyclic ligand pyrazine: Kinetic and mechanistic studies - Chatterjee, Debabrata; van Eldik, Rudi (Journal Macroheterocycles, 2020)
Electron transfer reactions involving Ru(III) complexes pioneered by Nobel Laureate Henry Taube in the ‘late sixties’, has been an area of continued research for more than the past five decades. This review focuses on the research progress in the use of a Ru(III) complex containing the ‘edta’ ligand (edta4– = ethylenediaminetetraacetate) in electron transfer processes, and mainly covers the electron transfer reaction of [RuIII(edta)(pz)]– (pz = pyrazine) with biologically important reductants, viz. L-ascorbic acid, catechol, sulfite, sulfide and thiols, highlighting the authors’ own research work. The scope of this review is to contribute to the mechanistic understanding of electron transfer reactions of [RuIII(edta)(pz)]– with aforementioned biologically important electron donors, and to illustrate the preferential reaction pathway(s).
CRIS-Team Scopus Importer:2020-12-18
Keywords: Biologically important reductants; Electron-transfer; Pyrazine; Reaction mechanism; Redox reaction; Ru(edta)